Service Quality of Border Region Higher Education Libraries - Muhammad Nur; Marisa S.B. Seran (Pendidikan Administrasi Perkantoran, Universitas Negeri Makassar, 2019)
The quality of a qualified library makes the library as one of the centers of information for the general public. This study aims to determine how well the quality of library services, to find out how high the interest in reading students, and to determine the effect of the quality of college library services on strengthening the reading interest of students in the Library at the University of Timor Library UPT. This study uses a qualitative descriptive approach with a sample of 100 students. Data collection was carried out through observation, interview, documentation and questionnaire techniques. The data that has been collected is processed using descriptive statistical analysis techniques and inferential statistics. The results showed that the quality of library services at the University of Timor in the border area was in the quite good category with an average of 33.48. Student reading interest is in quite a good category with a mean value of 20, 56. The level of relationship or correlation between the quality of library services at the University of Timor in the border region to the interest in reading students at the University Library of Timor is in the strong category correlation with intervals of 0.60-0.799 means that the higher the quality of library services at the University of Timor in the border region, the higher the interest in reading students in the Library.